Utility of Intracardiac Echocardiography in the Early Experience of Transcatheter Edge to Edge Tricuspid Valve Repair. (October 2021) - Eleid, Mackram F.; Alkhouli, Mohamad; Thaden, Jeremy J.; Zahr, Firas; Chadderdon, Scott; Guerrero, Mayra; Reeder, Guy S.; Rihal, Charanjit S.
Abstract : Background: Tricuspid edge to edge repair (TEER) is a novel treatment for severe tricuspid regurgitation and is highly dependent on intraprocedural image quality. To date, transesophageal echocardiography (TEE) has been the primary imaging modality used to guide TEER. The role of intracardiac echocardiography (ICE) has not been assessed. The objective of this study was to describe the use and role of 2-dimensional ICE in the early experience of TEER. Methods: Consecutive patients undergoing TEER (with or without concomitant mitral repair) with off-label use of MitraClip (Abbott, Santa Clara, CA) were included in the study. Utilization of 2-dimensional ICE in comparison with TEE imaging were collected in each procedure through retrospective review of the procedural reports and images. Results: Of 42 TEER cases, ICE was used in 15 (36%) and concomitant mitral repair was performed in 37 (86%). ICE was increasingly used over time for TEER. ICE was able to visualize the tricuspid leaflets with high resolution and provided superior leaflet visualization to TEE in 40% of cases where it was used. Patients treated with ICE guidance tended to have a greater baseline severity of tricuspid regurgitation compared with patients treated with TEE guidance alone (8/15 [53%] massive or greater tricuspid regurgitation versus 6/27 [22%]; P =0.09). Degree of tricuspid regurgitation reduction was similar with TEE alone versus ICE plus TEE guidance (1.9±1.0 versus 2.1±1.1 grade reduction, P =0.28). Conclusions: ICE was increasingly used in the early experience of TEER over time. ICE facilitates leaflet visualization for grasping and is a useful adjunct to TEE during TEER.